1997
DOI: 10.1038/bjc.1997.559
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution HLA-DRB1 and DQB1 genotyping in Japanese patients with testicular germ cell carcinoma

Abstract: Summary We report for the first time the frequency distributions of HLA-DRB1 and -DQB1 genes in 55 patients with testicular germ cell carcinoma (TGC) using the modified PCR-RFLP method and compare the results with those for 1216 healthy Japanese control subjects. The modified PCR-RFLP method produced accurate, reproducible cleavage patterns that are easily discriminated. HLA-DRB1*0410 was the susceptibility allele (RR = 3.26, P = 0.006) and DQB1 *0602 appears to be a candidate protective allele (RR = 0.26, P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…This is not in concordance with the published data which indicated an increase in HLA-DQ4 antigen frequency as well as the increased frequency of HLA-DRB1*0405 and HLA-DQB1*0401 alleles among patients [15]. Recently, a high-resolution genotyping study in TGCT patients indicated HLA-DRB1*0410 (OR = 3.26) as a susceptibility allele and HLA-DQB1*0602 as a candidate protective allele (OR = 0.26) for TGCT [16]. We did not find an association between these alleles and TGCT in our group of patients.…”
Section: Resultssupporting
confidence: 76%
“…This is not in concordance with the published data which indicated an increase in HLA-DQ4 antigen frequency as well as the increased frequency of HLA-DRB1*0405 and HLA-DQB1*0401 alleles among patients [15]. Recently, a high-resolution genotyping study in TGCT patients indicated HLA-DRB1*0410 (OR = 3.26) as a susceptibility allele and HLA-DQB1*0602 as a candidate protective allele (OR = 0.26) for TGCT [16]. We did not find an association between these alleles and TGCT in our group of patients.…”
Section: Resultssupporting
confidence: 76%
“…To date, linkage studies on these regions have isolated only Xq27 as the locus for a gene (TGCT1) that may be responsible for familial clustering of testicular carcinoma 4. It is not clear whether the HLA regions harbor a hereditary testicular carcinoma gene: The data are controversial 27–33…”
Section: Discussionmentioning
confidence: 99%
“…4 It is not clear whether the HLA regions harbor a hereditary testicular carcinoma gene: The data are controversial. [27][28][29][30][31][32][33] Table 1 shows whether the genetic defects associated with the hereditary conditions lie in chromosomal regions that appear to be of interest in cytogenetic studies on testicular carcinoma. If there are correlations, then this may be another clue to a causal relation between testicular carcinoma and the genetic defect concerned.…”
Section: Discussionmentioning
confidence: 99%